2018 Vegetable Production Handbook Chapter 2: Fertilizer Management for Vegetable Production in Florida - Guodong Liu; Eric H. Simonne; Kelly T. Morgan; George J. Hochmuth; Shinsuke Agehara; Monica Ozores-Hampton; Rao Mylavarapu (EDIS)
This 7-page fact sheet is chapter 2 of the 2018 Vegetable Production Handbook. Written by Guodong Liu, Eric H. Simonne, Kelly T. Morgan, George J. Hochmuth, Monica Ozores-Hampton, Shinsuke Agehara, and Rao Mylavarapu, and published by the Horticultural Sciences Department, 2018.